2019
DOI: 10.1080/17482631.2019.1648945
|View full text |Cite
|
Sign up to set email alerts
|

Dietary strategies and food practices of pediatric patients, and their parents, living with inflammatory bowel disease: a qualitative interview study

Abstract: Purpose: A growing body of scientific evidence supports the role of food and diet in the pathogenesis and management of inflammatory bowel diseases (IBD). However, little is known about the role of food and diet from the perspectives of pediatric patients and their parents. This study aimed to explore how children and adolescents with IBD and their parents coped with the illness through food and diet in their daily lives. Methods: We conducted semi-structured interviews with 28 children and adolescents with IB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(27 citation statements)
references
References 36 publications
0
27
0
Order By: Relevance
“…The most common gastrointestinal symptoms of PIBD are fatigue and abdominal pain in CD and rectal bleeding and diarrhea in UC (Perler et al, 2019). Other symptoms include frequency and urgency, loss of appetite and weight loss (Chuong, Haw, Stintzi, Mack, & O'Doherty, 2019). Those participants with less severe disease, or for whom treatment was very successful, were barely affected by ongoing symptoms, but some had to constantly watch for signs of imminent 'flare-ups'.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The most common gastrointestinal symptoms of PIBD are fatigue and abdominal pain in CD and rectal bleeding and diarrhea in UC (Perler et al, 2019). Other symptoms include frequency and urgency, loss of appetite and weight loss (Chuong, Haw, Stintzi, Mack, & O'Doherty, 2019). Those participants with less severe disease, or for whom treatment was very successful, were barely affected by ongoing symptoms, but some had to constantly watch for signs of imminent 'flare-ups'.…”
Section: Discussionmentioning
confidence: 99%
“…Those participants with less severe disease, or for whom treatment was very successful, were barely affected by ongoing symptoms, but some had to constantly watch for signs of imminent 'flare-ups'. Several were careful about their diets and followed typical dietary strategies to manage PIBD (Norton et al, 2012;Devlen et al, 2014;Chuong et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Many participants expressed a good understanding of the potential mechanisms of action of EEN in inducing remission in CD. Patients perceive food and diet as important in their condition and often employ dietary related strategies and modifications to help manage symptoms and control inflammation ( 30–33 ) . Previous studies have found that implementation of dietary changes is often guided by the patient’s anecdotal experience and research.…”
Section: Discussionmentioning
confidence: 99%
“…Diet was also identified as a top priority research question in a Canadian survey and meeting, highlighting that it is an important topic among families impacted by IBD, and a source of concern and stress [ 25 ]. A qualitative study of children with IBD and their families found that most used the identification of specific foods that influence symptoms or trigger flare-ups as a means of coping with IBD [ 26 ]. This can lead to food avoidance or exclusion diets in children and adolescents with IBD, which may or may not be necessary and can negatively impact nutritional status [ 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…This can lead to food avoidance or exclusion diets in children and adolescents with IBD, which may or may not be necessary and can negatively impact nutritional status [ 27 ]. However, this study also found that families emphasized healthy eating in addition to avoidance or moderation of trigger foods, especially due to the difficulty of remaining adherent to exclusion diets (e.g., specific carbohydrate diet) [ 26 ]. Similar research among adults with IBD found that adults struggle significantly with decisions about diet, often related to uncertainty of whether a food will exacerbate symptoms or disease, and encounter challenges with abstaining from foods [ 28 ].…”
Section: Introductionmentioning
confidence: 99%